Injuries to athletes with disabilities - Ferrara, M. S.; Peterson, C. L. (Sports Medicine, 2000)
Participation in sport activities for people with disabilities continues to gain in popularity. With participation in sports, there is an inherent risk of injury. A review of current sport epidemiological studies was used and we concluded that injury patterns for this population are similar to those for athletes without disabilities. Injury data from Paralympic competitions dating back to 1976 indicate that most elite athletes with disabilities seek medical care for illness and musculoskeletal injuries. However, there are very limited injury data regarding Winter Paralympic events or skiing injuries. For those athletes who participate in Summer Paralympic events, abrasions, strains, sprains and contusions are more common than fractures and dislocations. However, location of injuries appears to be disability and sport dependent. Lower extremity injuries are more common in ambulatory athletes (visually impaired, amputee, cerebral palsy) and upper extremity injuries are more frequent in athletes who use a wheelchair. While it appears that the majority of the injuries occurring in this population are minor in nature, inconsistencies in the definition of injury in the literature make this conclusion tenuous. When injuries are expressed as time lost in participation, 52% of injuries resulted in 7 days lost or less, 29% in 8 to 21 days lost and 19% in greater than 22 days lost. The only prospective study addressing injury rates of athletes with disabilities in a manner consistent with other sport epidemiological studies found an injury rate of 9.3 injuries per 1000 athlete-exposures (AE). This injury rate is less than American football (10.1 to 15/1000 AE) and soccer (9.8/1000 AE), and greater than basketball (7.0/1000 AE). It is unclear whether comparative statistics such as these take into consideration the number of illness and injury episodes that resulted from the disability. Further complicating epidemiological studies for athletes with disabilities is the definition of the population and samples of convenience which are frequently used. These samples are often not representative of the multiplicampity of disability conditions, levels of competition and range of sport activities available. Prospective studies comparing athletes to sedentary control individuals to measure differences in injury rates, type and frequency between and within disability groups, sports and levels of competition are desperately needed to further the knowledge of injury trends and develop and establish accurate injury prevention programmes.